The effects of regular exercise on anxiety, depression and quality of life in adult alcohol and drug dependents in addiction treatment - KARAGÖZOĞLU, CENGİZ (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2016)
Objective: The purpose of this study was to examine the effects of moderate-intensity aerobic and strength exercises on anxiety, depression, and quality of life of individuals with alcohol and substance addiction disorder during addiction treatment. Methods: This is a quasi-experimental design research. Depression, anxiety and quality of life of participants were assessed at baseline and at the end of the study and compared the difference between exercise and control group. The Bruce Treadmill Test was used to measure the predicted maxVO(2) to examine the changes in aerobic capacity and the four to six repetition submaximal strength test was used to measure the predicted one repetition maximal strength of the participants in the exercise group. Resting heart rate and blood pressure were also monitored. Results: Anxiety scores of exercisers was significantly lower than control group at the end of the study. Depression level of exercisers was also lower than control group but the difference was insignificant. Significant improvement has been found in the physical functioning, general health and vitality scores on subscales of quality of life of exercise group at the end of the study. A significant increase has been found in aerobic capacity and strength in the exercise group after the exercise intervention. Conclusions: This study is one of the first to examine the effects of both moderate-intensity aerobic and strength exercises on anxiety, depression and quality of life in adult alcohol and drug dependents' in addiction treatment in Turkey.
Keywords: dependence; anxiety; depression; exercise; quality of life; INTERVENTION